A development plan for the Reading Center at Barangay Pundaquit, San Antonio, Zambales - Ventura, Aries Joy T.; Santos, Yhna Therese P.; Obille, Kathleen Lourdes B. (Quezon City School of Library and Information Studies, University of the Philippines, Diliman, 2018)
Throughout the years, establishing public libraries have been a longtime phenomenon initiated by professionals in the field of Library and Information Science (LIS). However, like the profession itself, public libraries have been pursuant of justifying their societal and economic value for the people in the communities it is meant to serve.

This project aimed to create a Development Plan for the proposed Barangay Reading Center at Barangay Pundaquit, San Antonio, Zambales. The proponent follows an explanatory sequential and mixed methods research design in assessing the residents’ reading habits, interests, and information needs. The survey method, through the distribution of questionnaires, was conducted among 340 residents; whereas 12 of its respondents were invited to a Focus Group Discussion. A semi-structured interview with both the outgoing and newly elected Barangay Chairman was conducted on separate occasions.

Findings revealed that the residents have positive perceptions on establishing a barangay reading center in their area. Majority of the respondents were between 16-20 years old, predominantly female, and are students. There were four major benefits of the barangay reading center that emerged from the participants’ responses: 1) support education, 2) lifelong learning, 3) reading engagement, and 4) a new habit for the residents. Most of the residents desired books, newspapers, computer units, and conducive facilities for the above-mentioned project.

The results led to recommendations concerning the use of the designed Development Plan for the proposed barangay reading center. All findings were considered and integrated with the CDP and LOM. Due to dearth of professional librarians in the country, the proponent recommends that the LGU officials must at least consult a registered librarian in overseeing the collection and its development. With the presence of the proposed CDP and LOM, the assigned personnel will be able to manage the collection and services in accordance with the established standards. Collaboration with partner agencies are also suggested to create linkages and networks in promoting the reading center’s collection and services.
Vita.
Special Problem
Keywords: Barangay Reading Center -- Zambales -- San Antonio -- Barangay Pundaquit